Prevalence and Therapeutic Management of Infections by Multi-Drug-Resistant Organisms (MDROs) in Patients with Liver Cirrhosis: A Narrative Review - Lorenzo Onorato; Caterina Monari; Salvatore Capuano; Pierantonio Grimaldi; Nicola Coppola (MDPI AG, 2022)
Bacterial infections are common events that significantly impact the clinical course of patients with cirrhosis. As in the general population, infections caused by multi-drug-resistant organisms (MDROs) are progressively increasing in cirrhotic patients, accounting for up to 30-35% of all infections. Nosocomial acquisition and prior exposure to antimicrobial treatment or invasive procedures are well-known risk factors for MDRO infections. Several studies have demonstrated that infections due to MDROs have a poorer prognosis and higher rates of treatment failure, septic shock, and hospital mortality. Due to the increasing rate of antimicrobial resistance, the approach to empirical treatment in cirrhotic patients with life-threatening infections has become significantly more challenging. In order to ensure a prompt administration of effective antibiotic therapy while avoiding unnecessary antibiotic exposure at the same time, it is of utmost importance to choose the correct antimicrobial therapy and administration schedule based on individual clinical characteristics and risk factors and rapidly adopt de-escalation strategies as soon as microbiological data are available. In the present paper, we aimed to provide an overview of the most frequent infections diagnosed in cirrhotic patients, the prevalence and impact of antimicrobial resistance, and potential therapeutic options in this population.